Energy potential of Paulownia and Miscanthus clones for energy production in Chile - Pegoretti, Hector; Muñoz, Fernando; Teixeira, Regis; Sáez, Katia; Segura, Cristina; Olave, Rodrigo (Instituto de Ecología, A.C., 2020)
The global energy model is based on fossil fuels, which has been replaced by environmental and economic considerations, giving way to biomass and dendroenegetic plantations. In Chile, non-conventional renewable energies (NCRE) have been gaining space, and the nation has focused efforts on species with good energy potential. Thus, this study aims to evaluate the physical-chemical potential, energy and thermal profiles of two species (Paulownia elongata x fortunei and Miscanthus x giganteus) for energy use in three contrasting sites of Chile. The analyses were mostly performed under DIN Standards. The results for Paulownia showed differences between the sites, obtaining the best results in the Vergel site with a percentage of lignin of 34,84%, ashes of 1,16%, volatile material of 81.70%, carbon of 47.02% and a liquid energy density (EL) of 2.16 GJ m-3. For Miscanthus, the best results were also recorded in the Vergel, with a percentage of lignin of 30.60%, ashes of 2.84%, volatile material of 82.26% and carbon of 45.97% and a DEL of 1, 67 GJ m-3, highlighting that the best results of the Vergel site are for density D1. With respect to the thermal profile (TGA-DTG), Paulownia presented mass loss greater than Miscanthus and had ignition at a lower temperature of 197.76 °C and 209.66 °C respectively. Therefore, the highest percentage of waste was presented by Miscanthus with 5.63%. Accordingly, both species have desirable characteristics for their energetic use.